Novel mouse models for tracing brain-derived extracellular vesicles - Qi Wu; Fanxiu Ma; Meng Yuan; Xiumei Jin; Zhaodi Jiang; Jiyan Ma (Extracellular Vesicle)
Extracellular vesicles (EVs), particularly small extracellular vesicles (sEVs) such as exosomes, are carriers of biomolecules that reflect the metabolic status of host cells. Recently, sEVs have emerged as potential reservoirs of molecular biomarkers associated with pathological conditions, including cancers, neurodegenerative disorders, and cardiovascular diseases. While blood-based tests are common diagnostic tools, their efficacy in identifying central nervous system (CNS) diseases is significantly hindered by the blood-brain barrier, which prevents the entry of brain-derived proteins into the bloodstream. Capturing brain-derived sEVs (BDEs) in peripheral blood is a potential alternative for detecting CNS disease biomarkers. However, the presence of BDEs in blood remains obscure due to the lack of specific labeling. To address this challenge, we established two novel mouse models in which neuron-derived sEVs or EVs from specific brain regions were fluorescently labeled. Using these approaches we successfully detected fluorescently labeled EVs in both BDEs and plasma-derived sEVs (PDEs), confirming that BDEs are indeed present in peripheral blood. These models will serve as valuable tools for developing novel methods to efficiently capture BDEs in peripheral blood.